2021
DOI: 10.1152/ajpgi.00204.2021
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock core component Bmal1 dictates cell cycle rhythm of proliferating hepatocytes during liver regeneration

Abstract: Following partial hepatectomy (PH), the majority of remnant hepatocytes synchronously enter and rhythmically progress through the cell cycle for three major rounds to regain the lost liver mass. Whether and how the circadian clock core component Bmal1 modulates this process remains elusive. We performed PH on wild-type and hepatocyte-specific Bmal1 knockout (Bmal1hep-/-) mice and compared the initiation and progression of the hepatocyte cell cycle. After PH, wild-type hepatocytes exhibited three major waves of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Clock/Bmal1-dependent Nrf2 regulation gives rise to diurnal patterns in Nrf2 signaling, which underlies the rhythmic expression of antioxidant and metabolic enzymes. In the mouse knockout model, Bmal/absence in hepatocytes caused the activation of redox sensor Nrf2 [ 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clock/Bmal1-dependent Nrf2 regulation gives rise to diurnal patterns in Nrf2 signaling, which underlies the rhythmic expression of antioxidant and metabolic enzymes. In the mouse knockout model, Bmal/absence in hepatocytes caused the activation of redox sensor Nrf2 [ 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence have shown that hepatic clocks are critical mediators of glucose homeostasis since most of the binding sites were located/mapped in promoter areas of genes related to the metabolism of hepatic glucose (like Glut2 and G6pc ) and lipid (such as Agpat6 and Dgat2 ). This finding is supported by the in vivo test observation that showed mice with a liver-specific deletion of Bmal1 exhibit systemic glycemia and glucose intolerance due to the absence of rhythmic regulation of glucose metabolism related genes (e.g Glut2 ) ( 146 , 147 ). Newer studies built on these observations, demonstrating that hepatic Bmal1 is essential for controlling hepatic oxidative capacity through orchestrating intracellular mitochondrial dynamics such as mytophagy and fission ( 146 , 148 ).…”
Section: Diabetes and The Circadian Rhythm: A New Frontier In Diabete...mentioning
confidence: 63%
“…This finding is supported by the in vivo test observation that showed mice with a liver-specific deletion of Bmal1 exhibit systemic glycemia and glucose intolerance due to the absence of rhythmic regulation of glucose metabolism related genes (e.g Glut2 ) ( 146 , 147 ). Newer studies built on these observations, demonstrating that hepatic Bmal1 is essential for controlling hepatic oxidative capacity through orchestrating intracellular mitochondrial dynamics such as mytophagy and fission ( 146 , 148 ).…”
Section: Diabetes and The Circadian Rhythm: A New Frontier In Diabete...mentioning
confidence: 63%
“…We then sought to confirm our TRAP findings with small-molecule fluorescent RNA ISH (RNAscope). We initially focused on Bmal1 expression as it is an essential, nonredundant component of the mammalian circadian clock ( Haque et al, 2019 ) and is an integral regulator of circadian physiology in several cell types ( Lefta et al, 2012 ; Jiang et al, 2021 ). Cortical NG2-glia, identified by Cspg4 + nuclei, demonstrated increased Bmal1 RNA expression at a circadian time of day near the expected peak of Bmal1 expression (CT 0000) versus the daily nadir (CT 1200; Fig.…”
Section: Resultsmentioning
confidence: 99%